Evaluation of Domestic Airport Service Quality in Nepal - Thakuri, Diwash Malla; Adhikari, Guru Datta; Kalika, Swopnil (Journal on Transportation System and Engineering, 2025)
This study aims to assess the service quality of domestic airports in Nepal by focusing on passenger expectations and experiences. The Airport Service Quality (ASQ) dimensions developed by the Airports Council International (ACI) were used to analyse perceived service quality. Through confirmatory factor analysis, 15 key determinants of passenger satisfaction were identified under six ASQ dimensions. The study also examines the relationship between these service quality dimensions and overall passenger satisfaction, while identifying superior and inferior services at each airport. The findings are intended to assist policy-makers and airport managers improve the quality of airport services by understanding the needs and expectations of airport users.